FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA ANEMIA PADA IBU HAMIL TRIMESTER III DI PUSKESMAS SRIKATON - Suci, Dewi Tiara; Mastina; Merisa Riski; Erma Puspita Sari (LPPM STIKes Mitra Adiguna, 2024)
The World Health Organization (WHO) 2020, stated that maternal mortality is very high. In 2020 the maternal mortality rate during and after pregnancy and childbirth was around 295,000. One of the causes of maternal death due to complications during and after birth and childbirth is anemia. Risk factors that increase the incidence of anemia include pregnancy spacing, adherence to taking fe tablets, anc visits. Research Objective To determine the factors that influence the occurrence of anemia in third trimester pregnant women at the Srikaton Health Center, Banyuasin Regency in 2023. The study used an analytical survey method with a cross sectiona approach. The population in this study is all third trimester pregnant women listed in the medical record of the Srikaton Health Center, Banyuasin Regency in 2023 with a total of 70 people. Sempel collection using random sampling method. The results of the study found a significant relationship between pregnancy distance (p-value = 0.001 and OR 20.250), adherence to consumption of fe tablets (p-value = 0.000 and OR = 34.850), ANC visits (p-value = 0.009 and OR = 5,133) with the incidence of anemia in pregnant women at the Srikaton Health Center, Banyuasin Regency in 2023. Suggestions are expected to increase the knowledge of pregnant women about anemia problems so as to prevent the occurrence of anemia in pregnant women, especially pregnant women who have risky pregnancy spacing, have poor consumption of fe tablets, and have poor ANC visits. Keywords : Pregnancy Spacing, Fe Tablet Consumption Adherence, Anc Visit.